Effect of Advanced Glycation End Products on Human Thyroglobulin’s Antigenicity as Identified by the Use of Sera from Patients with Hashimoto’s Thyroiditis and Gestational Diabetes Mellitus - A. Hatzioannou; I. Kanistras; E. Mantzou; E. Anastasiou; M. Peppa; V. Sarantopoulou; P. Lymberi; M. Alevizaki (International Journal of Endocrinology)
Advanced glycation end products (AGEs) are formed on proteins after exposure to high concentrations of glucose and modify protein’s immunogenicity. Herein, we investigated whether the modification of thyroglobulin (Tg) by AGEs influences its antigenicity and immunogenicity. Human Tg was incubated in vitro with increasing concentrations of D-glucose-6-phosphate in order to produce Tgs with different AGE content (AGE-Tg). Native Tg and AGE-Tgs were used in ELISA to assess the serum antibody reactivity of two patient groups, pregnant women with gestational diabetes (GDM), and patients with Hashimoto’s thyroiditis (HT). We produced in vitro AGE-Tg with low and high AGE content, 13 and 49 AGE units/mg Tg, respectively. All HT patients’ sera presented the same antibody reactivity profile against native Tg and AGE-Tgs, indicating that the modification of Tg by AGEs did not alter its antigenicity. Similarly, the GDM patients’ sera did not discriminate among the two forms of Tg, native or artificially glycated, suggesting that the modification of Tg by AGEs might not alter its immunogenicity. The modification of Tg by AGEs has no obvious effect on neither its antigenicity nor, most likely, its immunogenicity. It seems that other Tg modifications might account for the production of aTgAbs in patients with GDM.